2007
DOI: 10.1111/j.1365-2486.2007.01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Summer heatwaves promote blooms of harmful cyanobacteria

Abstract: Dense surface blooms of toxic cyanobacteria in eutrophic lakes may lead to mass mortalities of fish and birds, and provide a serious health threat for cattle, pets, and humans. It has been argued that global warming may increase the incidence of harmful algal blooms. Here, we report on a lake experiment where intermittent artificial mixing failed to control blooms of the harmful cyanobacterium Microcystis during the summer of 2003, one of the hottest summers ever recorded in Europe. To understand this failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
592
4
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 882 publications
(646 citation statements)
references
References 76 publications
20
592
4
11
Order By: Relevance
“…The increase in surface water temperatures and the length of thermal stratification as a direct response to increased water temperatures coincided with higher abundance of cyanobacterial bloom in Lake Karaoun (Figure 4). This is in agreement with other studies those reported that climate warming may favour the growth and abundance of cyanobacterial species which are well adapted to higher temperatures and stratified conditions as well [21][22] . Moreover, the stratification period was coincided with low epilimnion nutrient concentrations in the lake.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The increase in surface water temperatures and the length of thermal stratification as a direct response to increased water temperatures coincided with higher abundance of cyanobacterial bloom in Lake Karaoun (Figure 4). This is in agreement with other studies those reported that climate warming may favour the growth and abundance of cyanobacterial species which are well adapted to higher temperatures and stratified conditions as well [21][22] . Moreover, the stratification period was coincided with low epilimnion nutrient concentrations in the lake.…”
Section: Discussionsupporting
confidence: 83%
“…Changes in plankton community as a result of global warming are a growing concern in ecological studies, as those properties substantially contribute to ecosystem functioning [21][22][23]. According to Paerl et al [24], climate change can result in modified patterns, intensities and duration of precipitation and droughts.…”
Section: Discussionmentioning
confidence: 99%
“…Direct effects, such as rising temperatures, and indirect effects, such as intensified stratification, favor cyanobacterial blooms. Increased water temperature is expected to give cyanobacteria a selective advantage over competing phytoplankton because of the high optimal growth temperature of cyanobacterial species (Elliott et al, 2006;Jöhnk et al, 2008). Laboratory studies on Microcystis aeruginosa have demonstrated increasing growth rates with increasing temperatures from 20 to 32 C (van der Westhuizen and Eloff, 1985;Watanabe and Oishi, 1985;Imai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication and climate change cause massive growth of cyanobacteria in water bodies across the world (Jöhnk et al 2008;Paerl and Huisman 2008). Several publications presented in this special issue of Aquatic Ecology entitled ''Cyanobacterial bloom.…”
Section: Introductionmentioning
confidence: 99%